United Nations Commission on International Trade Law (UNCITRAL) Yearbook 2011 - United Nations (United Nations, 2014)
The United Nations Commission on International Trade Law (UNCITRAL) is the core legal body of the United Nations system in the field of international trade law. It specializes in the modernization and harmonization of rules on international business. This publication reproduces the substantive documents prepared each year for the Commission and its working groups, and is divided into three parts. Part One deals with the Commission’s report. Part Two covers studies and reports on specific subjects. Part Three contains meeting records, the bibliography and checklists of UNCITRAL documents prepared in the current and previous years. It also includes General Assembly resolutions and Sixth Committee reports related to UNCITRAL’s work.